Strategi Bisnis dan Pemasaran Inovatif untuk Lemang Tapai sebagai Kuliner Tradisional Bernilai Ekonomis - Lestari, Egi Sri; Fauziah, Dzamratul; Rahmahnusiya, Elvina Triya; Aszahrah, Radiah; Hasanah, Uswatun (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Lemang Tapai is one of Indonesia's traditional culinary delights which has high economic potential. However, limitations in business and marketing strategies often become obstacles for business actors in increasing competitiveness and expanding markets. This community service activity aims to provide assistance to business actors in developing innovative business and marketing strategies that can increase the selling value of Lemang Tapai. The methods used include training, mentoring, and evaluation of the implementation of digital marketing strategies, product diversification, and more attractive packaging. The results of this program show that with the implementation of digital-based marketing strategies and innovation in packaging and product variants, there has been an increase in demand and wider market reach. Thus, innovative business and marketing strategies are proven to be able to increase the economic value of Lemang Tapai and empower local business actors.